Índices biométricos e fisiológicos em feijoeiro sob diferentes doses de adubação fosfatada - Zucareli, Claudemir; Ramos Junior, Edison Ulisses; de Oliveira, Mariana Alves; Cavariani, Cláudio [UNESP]; Nakagawa, Joao [UNESP] (Universidade Estadual de Londrina (UEL), 2010)
The study had the objective of evaluate the growth of bean cultivar Carioca early cultivated during the rainy season under different doses of phosphorus applied to soil. We adopted the experimental design at random blocks, evaluating six doses of phosphorus (0, 30, 60, 90, 120 and 150 kg P(2)O(5) ha(-1)), relying in the form of superphosphate triple, with five replicates. Biometric indices were evaluated leaf area (cm(2) plant(-1)) and dry matter (g seedling(-1)). Physiological indices of crop growth rate (CGR, g m(-2) day(-1)), relative growth rate (RGR, g g(-1) day(-1)), net assimilation rate (NAR, g m(-2) day(-1)), leaf area ratio (LAR, cm(2) g(-1)) and specific leaf area (SLA, cm(2) g(-1)) were obtained through analysis of functional growth. The data from the biometric indices were submitted to analysis of variance, with subsequent construction of regression models. The dry matter and leaf area of bean Carioca Early increase linearly with increasing doses of applied phosphorus in the soil. The dry matter has increased constantly throughout the cycle, and the leaf area indices reach its maximum at 52 days after emergence (DAE). The restriction of phosphorus reduces the Relative Growth Rate at the beginning of the development and lengthen the physiological cycle of bean cultivar Carioca early.
Physiological and biometric indices in bean under different doses of phosphorus
Keywords: Phaseolus vulgaris; Fertilization; Phosphorus; Growth analysis